A study of the effect of substrate on dot-matrix printing - Saini, Komal; Singh, Varinder; Kaur, Manpreet; Sharda, Seema (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
A study related to Dot-matrix printers has been carried out in order to analyze the effect of change of substrate on its printing characteristics. Twenty Dot-matrix printers and five types of substrates or white pages have been selected for the study. The printouts have been taken on all the five types of white papers from each of the twenty Dot-matrix printers. These printouts have been examined using stereomicroscope 4x40magnification and VSC 2000 C to examine the features such as change in colour of ink, lustre of printing text, impact of printing, spreading of ink, background noise, UV fluorescence and absorption spectra. It has been concluded that the physical characteristics of dot-matrix printing gets changed by changing the type of substrate even in case of the same printer. Thus, the results of this study would definitely help the forensic document examiners to give an accurate opinion on the cases related to Dot-matrix printouts, specifically in the examination of multiple documents consisting of different types of papers.
Keywords: drukarka igłowa; dokumenty; charakterystyka druku; mikroskop stereoskopowy; VSC 2000C